A Decade of Fundamental Movement Skills in Elementary Schools: A Bibliometric Study Scopus Database 2014-2023 - Ismaiedh Cukarso, Sulthan Hadist; Sujarwo; Setiakarnawijaya, Yasep; Subandi, Oman Unju (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Fundamental movement skills are very important and have an impact on children’s development. This research aims to explore and analyze articles related to fundamental movement skills in elementary schools over the last decade through a bibliometric study in order to explore a research roadmap regarding fundamental movement skills in elementary schools. This bibliometric study takes four stages, namely: (1) searching for articles; (2) classifying articles; (3) checking and completing article metadata; and (4) carrying out bibliometric analysis. This study explores seven findings related to (1) publication trends in fundamental movement skills in elementary schools in 2014-2023; (2) citation trends for fundamental movement skills in elementary schools in 2014-2023; (3) author collaboration that has the strongest link to publications on fundamental movement skills in elementary schools in 2014-2023; (4) Development of author keywords in publications onfundamental movement skills in elementary schools in 2014-2023; (5) Development of abstracts on publications on fundamental movement skills in elementary schools in 2014-2023; (6) institutional collaboration on the publication of fundamental movement skills in elementary schools in 2014-2023; and (7) Distribution of countries that contributed to the publication of fundamental movement skills in elementary schools in 2014-2023. Based on these seven findings, it can be concluded that there is a lack of attention from academics and researchers to fundamental movement skills in elementary schools. This can be seen from the very minimal number of publications in the last decade